2004
DOI: 10.1002/marc.200300298
|View full text |Cite
|
Sign up to set email alerts
|

Hyperbranched Polyesters Based on Adipic Acid and Glycerol

Abstract: Summary: Hyperbranched polyesters with controlled molecular weights and properties have been prepared by an A2 + B3 approach by reacting glycerol and adipic acid without any solvents in the presence of tin catalysts. The hyperbranched polyesters have been evaluated by size exclusion chromatography (SEC) analysis and NMR spectroscopy in order to determine molecular weights and degrees of branching.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
153
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 128 publications
(165 citation statements)
references
References 18 publications
12
153
0
Order By: Relevance
“…7 Limited availability of AB n monomers increases the use of readily available A 2 þ B 3 monomers for the synthesis of HBP. 8,[9][10][11] After preliminary work by Kim 12 on hyperbranched liquid crystalline polymers, (HBLCPs), synthesized by the AB n approach, the revolutionary work in this field was carried out by Percec et al, [13][14][15][16][17][18] Shibaev et al, 19 and others [20][21][22][23] have reported on photo-addressable dendritic polymers (PADLCPs) containing both mesogenic and photochromic groups. PADLCPs have shown enhanced physicochemical properties and photo and thermally induced physical changes as compared with linear polymers.…”
Section: Introductionmentioning
confidence: 99%
“…7 Limited availability of AB n monomers increases the use of readily available A 2 þ B 3 monomers for the synthesis of HBP. 8,[9][10][11] After preliminary work by Kim 12 on hyperbranched liquid crystalline polymers, (HBLCPs), synthesized by the AB n approach, the revolutionary work in this field was carried out by Percec et al, [13][14][15][16][17][18] Shibaev et al, 19 and others [20][21][22][23] have reported on photo-addressable dendritic polymers (PADLCPs) containing both mesogenic and photochromic groups. PADLCPs have shown enhanced physicochemical properties and photo and thermally induced physical changes as compared with linear polymers.…”
Section: Introductionmentioning
confidence: 99%
“…Through the NMR spectra and the study described by Stumbo and Bruchmann, 19 it was possible to propose structures of resins. Beside, the ChemBioDraw software were used to simulate the spectra of 1 H NMR.…”
Section: Resultsmentioning
confidence: 99%
“…The values of Mw and PDI were lower than those found by Stumbo and Bruchmann. 19 MALDI-TOF spectrum of GAF and GUF resins are shown in Figure 2. It could make a size estimate of the resins chain from the Mw and GAF resin is approximately 15 monomers whereas the monomer is 74 Da per unit, ant they may correspond to a fragment from the glycerin.…”
Section: Resultsmentioning
confidence: 99%
“…Reactions were performed under dry conditions using a Schlenk line, Schlenk flasks, and argon as the inert gas. 13 C NMR spectra were recorded on a Bruker AMX 500 (Bruker Corporation, Billerica, MA, USA), Jeol ECP 500 (JEOL (Germany) GmbH, Freising, Germany), or a Bruker Avance 400 spectrometer (Bruker Corporation, Billerica, MA, USA) (at 295 K). Inverse-gated 13 C NMR and overnight measurements spectra were recorded on a Bruker Avance 500 spectrometer, or a Bruker Avance III 700 (Bruker Corporation, Billerica, MA, USA).…”
Section: Methodsmentioning
confidence: 99%